The Impact of Indoor and Outdoor Experiential Learning on Academic Achievement in Primary School - Christian, Erica Wahyu; Tarihoran, Naf’an; Sapriati, Amalia (Indonesian Journal of Instruction, 2024)
The low standard deviation in science scores suggests a considerable number of students with below-average performance, highlighting the need for more effective teaching strategies. This situation calls for a re-evaluation of the methods used in science education. This study aims to evaluate the impact of experiential learning approaches (indoor and outdoor) on the academic achievement of elementary school students, especially on the science learning outcomes of fifth grade students. The method used is quantitative with an experimental design, where two control groups are compared: class VA using outdoor learning and class VB using indoor learning. This study involved a pre-test and a post-test to measure the development of students' science learning outcomes after the learning intervention. The results showed a significant correlation between experiential learning strategies and academic achievement. The data indicated that both male and female students showed better grades when learning using the outdoor approach compared to indoor. In conclusion, although there was no interaction effect between learning strategies and gender, there was a significant difference in academic achievement between students who participated in outdoor learning and those who participated in indoor learning. Outdoor learning has been shown to be more effective in improving science learning outcomes than indoor learning.